Spinning the legs and blood: should intradialytic exercise be routinely offered during maintenance haemodialysis? - Graham-Brown, Matthew P M; Herrington, William G; Burton, James O (Clinical Kidney Journal, 2021)
Patients with end-stage kidney disease on haemodialysis (HD) have an elevated risk of cardiovascular disease (CVD). These patients also experience high levels of physical deconditioning and programmes of rehabilitation have been tested in a variety of forms with variable success. It has been suggested that programmes of exercise rehabilitation have a role to play in improving the physical condition of patients on HD and in addressing the traditional and non-traditional risk factors that drive CVD for this population. Intradialytic exercise has often been suggested as a convenient way of delivering rehabilitation for patients on HD, as it makes use of otherwise dead time, but there are legitimate concerns about this group of at-risk patients undertaking exercise at a time when their myocardium is already vulnerable to the insults of demand ischaemia from the processes of dialysis and ultrafiltration. A study in this issue of Clinical Kidney Journal provides reassuring data, showing that cycling during dialysis potentially reduces evidence of demand ischaemia (episodes of myocardial stunning). Together with the safety and quality of life data, we expect from the multicentre PrEscription of Intra-Dialytic Exercise to Improve quAlity of Life in Patients With Chronic Kidney Disease study (the protocol for which is published concurrently), rehabilitation programmes that include intradialytic exercise are perhaps closer than ever for patients on HD.